Ecology, Distribution And Behaviour Of Rove Beetle, Paederus fuscipes Curtis (Coleoptera: Staphylinidae) In Relation To Human Settings - Sufian, Maryam (2018)
Paederus fuscipes Curtis has garnered tremendous interesin recent years because it causes nasty skin lesion in humans in tropical countries. This study focuses on the biological and behavioural aspects, the interactions with human residential premises and the isolation of bacteria associated with P. fuscipes. In the study of predator-prey interaction, P. fuscipes showed a Type II functional response for all prey species. At the high prey density they consumed predominantly more on Recilia dorsalis Motschulsky. Among the prey species, R. dorsalis and Nilaparvata lugens Stål were commonly preferred by P. fuscipes as compared to Nephotettix virescens Distant due to their small and soft body characteristics.